Diagnosing gastrointestinal infections based on cycle threshold cut-offs of PCR - Rania Karam; Peter Kechker; Shifra Ken-Dror; Avi Peretz; Maya Azrad (Microbiology Spectrum)
ABSTRACT This study compared the performance of molecular vs stool culture assays for gastrointestinal infection (GII) detection, with focus on defining cycle threshold (Ct) cut-off values for positive culture results. A total of 6,000 records of patients with suspected GII between October 2022 and February 2023 and registered at Clalit HealthCare Services in Haifa, Israel, were reviewed. Stool samples were collected from all patients with suspected GII. PCR was performed with the Seegene Allplex GI-Bacteria (I) assay kit. PCR-positive samples were cultured on bacteria-specific agar media. Out of 356 PCR-positive samples, 196 (55.1%) were culture-positive. Significant differences were noted between the mean Ct of culture-positive vs culture-negative samples for Shigella spp. (P < 0.0001), E. coli O157 (P = 0.0001), and Campylobacter spp. (P = 0.004). Shigella had the lowest Ct cutoff (27.14). Negative culture results for PCR-positive samples may result from low bacterial load. At the same time, false-positive PCR results may exist. Thus, PCR result should be considered along with clinical presentation and with Ct value consideration.IMPORTANCEGII diagnostic procedures have shifted from traditional- to molecular-based assays, which may increase missdiagnosis due to the high PCR sensitivity and false positives. This study suggests to consider a Ct threshold for each pathogen in order to reduce inaccurate diagnosis. Alternatively, culture should be performed for PCR-positive samples.